Determinants of consumers’ choice behaviour for fresh fish types - Sina Basil Johnson; Ojuetimi Enitan Mafimisebi; Joseph Olukubun Ikuerowo; Orimisan Justin Ijigbade (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The demand for and supply of fresh fish in many developing countries in the world today Nigeria inclusive, are yet to satisfy the annual dietary needs of their citizenry. This phenomenon, therefore, put unresisting pressure on the need to identify and grow more fresh fish that can meet the socio-cultural and economic desires of consumers. In the light of this, the present study examines the determinants of consumers’ choice behaviour for fresh fish types in Nigeria. Primary data were collected from 360 household heads through a structured questionnaire using a multistage sampling procedure. Multinomial logit regression model (MNL) was employed to analyse the impacts of socio-economic and fish-specific attributes of consumer choice for fresh fish. Results showed that 81 per cent were female households with a mean age of 35 years and mean household size of 4 members. Mean years of schooling and monthly expenditure were 13 and ₦3,611.94 (USD10.01), respectively. Mean consumptions of fresh fish category were mudfish (0.3354), catfish (0.1889), tilapia (0.2167), trunk fish (0.1138) and snakehead fish (0.1444). The McFadden R2 was 0.50 and the validity of independence of irrelevant alternatives hypothesis for the use of MNL was not violated given a p-value of 0.7618. Results showed that consumers' income, price of the fish, level of education, household size, experience and freshness had a significant impact on fresh fish choices. The study therefore recommends that policy that will increase consumers’ satisfaction for every naira spent on fresh fish and improve fish qualities should be given proper attentions.